A perfluorinated moiety-grafted carbon nanotube electrode for the non-aqueous lithium–oxygen battery. Issue 19 (23rd December 2014) - Thomas, Morgan L.; Yamanaka, Keisuke; Ohta, Toshiaki; Byon, Hye Ryung
Abstract : A highly localized Li–O2 electrochemical reaction is demonstrated in close proximity to the perfluorinated moiety grafted to the carbon nanotube electrode. Abstract : A perfluorinated alkyl chain grafted to carbon nanotubes is employed in the lithium–oxygen (Li–O2 ) cell. We demonstrate a highly localized Li–O2 electrochemical reaction in close proximity to the perfluorinated moiety owing to its high O2 affinity. This hydrophobic modification can provide an enhancement in capacity for a very thin microbattery system.